Legenda Mbah Sogol dan Cikal Bakal Gondanglegi Malang - Khuzaimah Khuzaimah; Kholik Kholik (Khatulistiwa: Jurnal Pendidikan dan Sosial Humaniora, 2025)
This study describes a person who became a role model in the city of Gondanglegi "Mbah Sogol" who was the first person to establish a musolla in Gondanglegi, his place in Al kaustar. It is the custom of Muslims in Java when on a certain day all people visit the tomb to read prayers for the deceased krabat, there are also those who come to the religious scholars to take their barokah, one of which is Mbah Sogol who is visited by many people around him to pray for him because he is a spiritual figure who teaches Islam in Gondanglegi. There are some people who say that coming to eat a person is polyhistamine (associating with Allah) they do not know that pilgrimage is not to make offerings or to ask for pesugihan only. With the kindness of Mbah Sogol, all people usually come to the grave to give prayers to him. The technique of collecting stories is by interviewing one of the people of Gondanglegi who already knows very well about the history of Mbah Sogol, by the way he gives lessons about Islam in Gondanglegi, his character also gives trust to the community to deepen Islam in Gondanglegi. The team in tracing Mbah Sogol's identity obtained an idea that as many as 93 of Prince Diponegoro's war troops moved to the east by spreading to the areas of the resting place and settling by opening new residential areas, Mbah Sogol arrived in Gondanglegi by following the trail and serving three noble families from the Klaten area of Central Java, namely Raden Mas Joyo Soepeno, Raden Mas Joesoef, and Raden Ayu Arimbi.